Darcy Ribeiro e a Fundação da Universidade de Brasília: uma perspectiva histórica e educativa (1960-1964) - Fonseca, Marília Barbara da (2021)
This dissertation is the result of a study entitled “Darcy Ribeiro and the foundation of the University of Brasília: a historical and educational perspective (1960-1964)”. This research is linked to the Master's Program in Education of the Federal University of Uberlândia and follows the researches on the field of “History and Historiography of Education”. In its analysis, a historical contextualization of the educational process was carried out, with emphasis on the first half of the 1960s and scope in the utopia of the creation of the University of Brasília (UnB). It focused on the period between 1960, as it was the period of implementation of the university, and 1964 when a military coup interrupted the ideal present in the foundation of UnB. The path of the UnB is intertwined with the history of Brazil’s capital itself. The conception of the UnB was outlined in a project of intellectuals who have conceived education as a perspective of social change in the Brazilian scenario; much more than a project, it also meant a mission. Given this context, this study aimed to analyze the educational precepts defended by Darcy Ribeiro in the founding process of the University of Brasília (UB) from a historical and educational perspective. The methodology used is based on bibliographical and documentary research focusing on the work of Darcy Ribeiro, specifically concerning the creation of the aforementioned university. The documents and the investigated literature showed that bearing in mind the perspective of a human being in its wholeness, Darcy Ribeiro, together with other intellectuals and politicians, conceived the construction of the UnB, so that it would be “the mother, the ideal” of Brazilian universities. Thus, UnB was conceived based on our reality, an authentic Brazilian university, with the utopia of solving its problems it would be the necessary university since they believed in the university reform as an instrument to overcome Brazil's backwardness. Under its founder’s ideals, this institution would contribute to minimizing the stratification of society, as they have believed in quality, secular, and free public education, which would manage to integrate school and university, theory and practice, and which, fundamentally, could narrow the distance between the wealthy and the lower class. One of Darcy Ribeiro's concerns was the emancipatory education that people from the lower class should receive in public schools, within the scope of the humanist conception. We will also debate about the invasion of the UnB by military troops and the consequences of the dictatorship, the diaspora of its professors, and the interrupted dream. In short, this study showed the conception of education in the ideas of Darcy Ribeiro exposed in the construction of UnB as a necessary university for Brazil